C‐terminal Cysteines of CueR Act as Auxiliary Metal Site Ligands upon Hg(II) Binding—A Mechanism To Prevent Transcriptional Activation by Divalent Metal Ions? - Balogh, Ria K. (Chemistry, 2019)
Intracellular Cu(I) is controlled by the transcriptional regulator CueR, which effectively discriminates between monovalent and divalent metal ions. It is intriguing that Hg(II) does not activate transcription, as bis‐thiolate metal sites exhibit high affinity for Hg(II). Here the binding of Hg(II) to CueR and a truncated variant, ΔC7‐CueR, without the last 7 amino acids at the C‐terminus including a conserved CCHH motif is explored. ESI‐MS demonstrates that up to two Hg(II) bind to CueR, while ΔC7‐CueR accommodates only one Hg(II). (199m)Hg PAC and UV absorption spectroscopy indicate HgS(2) structure at both the functional and the CCHH metal site. However, at sub‐equimolar concentrations of Hg(II) at pH 8.0, the metal binding site displays an equilibrium between HgS(2) and HgS(3), involving cysteines from both sites. We hypothesize that the C‐terminal CCHH motif provides auxiliary ligands that coordinate to Hg(II) and thereby prevents activation of transcription.